Top and bottom fermentation beer brewed with commercial buckwheat malt - Podeszwa, Tomasz; Harasym, Joanna; Czerniecki, Piotr; Kopacz, Magdalena (Engineering Sciences And Technologies, 2016)
The investigations of buckwheat malting and its usage for brewing were driven by the rising market demand for gluten–free beer. This has been extensively studied, leading to the conclusion that it is impossible to brew beer from 100% buckwheat malt without additional support from the added enzymes. The main problem was the resulting viscosity which has caused the rejection of this valuable raw material. Such an approach has led to the unjustified marginalization of this type of malt in brewing. As buckwheat malt also contributes to antioxidant activity when used in food formulation, it was reasonable to study its potential application in brewing. This study evaluates the top and bottom fermentation process conducted on 20% of commercially available buckwheat malt contribution. Such a contribution delivers the viscosity of wort within the acceptable range which does not cause further filtration problems. Sensory analysis revealed the high acceptability of the resulting beer, pointing simultaneously to the insufficient guidelines for assessments of such a novel beer
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2016, Nr 3 (22), s. 90-100
Keywords: buckwheat malt; Castle Malting; top fermentation; bottom fermentation; beer; słód gryczany; sława górska; fermentacja górna; fermentacja dolna; piwo